100 ideas for surviving your first year in teaching - Fisher, Laura-Jane. (London ; New York : Continuum, 2007)
Laura-Jane Fisher provides one hundred ideas on how to survive the first year of teaching. This book deals with a wide range of issues from coping with the long working hours and managing difficult classes to lesson planning and writing reports for the first time.
Keywords: First year teachers; Teaching; EDUCATION -- Teaching Methods & Materials -- General